Association between developmental coordination disorder or low motor competence, and risk of impaired bone health across the lifespan: protocol for a systematic review and meta-analysis. Issue 5 (7th May 2021) - Tan, Jocelyn; Hart, Nicolas H.; Rantalainen, Timo; Chivers, Paola
ABSTRACT: Objective: This systematic review will assess the association between developmental coordination disorder or low motor competence and impairments in bone health across the lifespan. Introduction: Individuals with developmental coordination disorder tend to have a pattern of physical activity associated with bone health impairments. Preliminary studies have found impairments in bone health measures, including fractures, throughout the lifespan with potential public health ramifications. As studies in this area are of small samples across wide age ranges, no comprehensive picture of bone health in this group has been formed, hindering action. A systematic review is needed to determine the potential risk of bone impairment in this population. Inclusion criteria: Studies that assess the relationship between developmental coordination disorder/low motor competence and bone health, regardless of measures used, will be included in the review. There will be no exclusions based on region, study design, or participant demographic characteristics. Methods: Published studies and gray literature will be searched, with no limits on publication date or language. Assessment of studies for inclusion, as well as data extraction, will be performed by two reviewers, with data cross checked for accuracy. Studies will be appraised using the appropriate JBI tool for the study design. Data to be extracted include unadjusted results and effect sizes for bone health measures. A narrative synthesis will be performed and if there is a sufficient number of studies, a meta-analysis using the same outcome measures will be performed on odds ratios of abnormal bone phenotype and fracture in this population. Systematic review registration number: PROSPERO CRD42020167301